Dielectric constant, dielectric loss and thermal conductivity of Si3N4 ceramics by hot pressing with CeO2–MgO as sintering aid. (January 2021) - Dai, Qijun; He, Daihua; Meng, Fancheng; Liu, Ping; Liu, Xinkuan
Abstract: Dense silicon nitride ceramic was sintered by hot pressing at 1800 °C for 3 h under the uniaxial pressure of 40 MPa in N2 atmosphere using CeO2 –MgO as sintering aid. In this study, the effect of the addition of CeO2 –MgO on the sintering of silicon nitride ceramics was investigated. The equiaxed α-Si3 N4 was transformed into a rod-shaped β-Si3 N4 completely by using XRD and SEM analysis. The sample reached a maximum density of 98.2% and a high flexural strength (872 ± 65 MPa). The range of dielectric constant is 10.79–11.06 (12.4 GHz), and the dielectric loss is in the order of 10 E −3 . The highest thermal conductivity achieved in all samples is 45.5 W/mK.